Effectiveness of a brief multicomponent intervention to improve physical activity level and functional capacity in fibromyalgia and chronic fatigue syndrome (Synchronize+) - Martín-Borràs, Carme; González Serra, Gemma; Carrasco-Querol, Noèlia; Sansano-Nadal, Oriol; Bueno Hernández, Nerea; Bestraten del Pino, Pau; Pastor Cazalla, Marta; Caballol Angelats, Rosa; Montesó-Curto, Pilar; Castro Blanco, Elisabet; Pozo Ariza, Macarena; Fernández-Sáez, José; et al. (Frontiers in Physiology, 2024)
IntroductionFibromyalgia (FM) and chronic fatigue syndrome (CFS) are complex central sensitization syndromes that represent an important public health problem. Low cardiorespiratory fitness and muscle function with habitual intolerance to efforts are common characteristics of FM and CFS. This study aimed to examine the effect of a brief multicomponent intervention based on physical activity (PA), nutrition, and chronobiology on movement behaviors (PA, sedentary and sleep time), muscle strength, and cardiorespiratory capacity.Methodsrandomized controlled trial was conducted in primary healthcare in Catalonia. A total of 143 individuals with FM or FM and CFS concomitantly (age 50.8, SD 8.1; 94.4% women) were randomly allocated to the intervention (IG, n = 69) or control (CG, n = 74) groups. The IG participated in a brief multicomponent (PA, nutrition, and chronobiology) group-based intervention (4 sessions, 3 h/session) while the CG received usual primary care practice. Primary outcome measure was PA measured by the REGICOR-Short Physical Activity Questionnaire. Secondary outcomes were sedentary (International Physical Activity Questionnaire) and sleep time (Pittsburgh Sleep Quality Index), upper- and lower-body muscle strength (handgrip and sit-to-stand test, respectively), and aerobic capacity (6-min walk test). Data were collected at baseline and 3 months post-intervention.ResultsThe IG showed positive differences at 3-month follow-up, with highly appreciably PA levels, less sedentary time, and significantly improved sleep time. Significant between-group differences were also observed at 3 months, with better health values in the IG: PA and sleep time (370.3 ± 307.0 vs. 195.9 ± 289.1 min/week and 6.1 ± 1.6 vs. 5.5 ± 1.8 h/night, respectively) and less sedentary time (266.2 ± 153.3 vs. 209.4 ± 199.9 min/day). The IG also showed higher upper limb strength and significant lower-body strength both between and within groups, as well as significantly improved cardiorespiratory capacity.ConclusionThe Synchronize + multicomponent program implemented at primary healthcare has shown short-term effectiveness in improving 24-h movement behaviors and health outcomes in individuals with FM, with or without CFS. This intervention may be a first step in educating and motivating people with FM and CFS to adopt an active lifestyle, leading to improved health. Long-term follow-up will determine whether the changes are maintained over time and their impact on quality of life and healthcare costs.